Gender and School-Type Differences in Food Preferences, Dietary Habits, and Influencing Factors among Gen Z Teenagers - Okadigwe John Chukwujekwu; Obi Rita Nkemjika (Journal of Social Science and Economics (JOSSE), 2025)
In recent years, the eating behaviors of Generation Z teenagers have become a growing concern for health educators, parents, and policymakers due to the rising influence of digital media, shifting cultural norms, and school environments. These factors, alongside gender and school type, shape how teenagers make food choices and perceive their health. This study investigated gender and school-type differences in food preferences, dietary habits, perceived health outcomes, and the influence of social, cultural, and digital factors among Generation Z teenagers in selected secondary schools in Anambra State, Nigeria. The study used a descriptive survey design to cover the perceptions among 150 Gen Z teenagers in selected public and private secondary schools in Anambra State, Nigeria. A multistage sampling method ensured balanced representation. Data were collected using a validated and reliable questionnaire (Cronbach’s Alpha = 0.84), reviewed by experts. Trained assistants administered the instrument during school hours. ANOVA and Tests of Between-Subjects Effects analyzed hypotheses using SPSS version 25 at a 0.05 significance level. The result showed no significant difference in food preferences among Gen Z teenagers based on gender and school type (F = 1.309, p = .274). However, school type significantly influenced how food preferences affected daily dietary habits (F = 4.580, p = .034). There was no significant relationship between dietary choices and perceived health outcomes (F = 0.286, p = .594), nor did social, cultural, and digital influences significantly shape food preferences (F = 0.695, p = .406). Female students in private schools reported higher influence from external factors (Mean = 3.10), while males showed more stable patterns across both school types. The study concludes that while school type plays a role in dietary behavior, gender differences are less pronounced. It recommends targeted nutrition education and health promotion strategies, particularly in public schools, to improve adolescent food practices and well-being.